Enhancing Healthcare Excellence: Unveiling Added Value in Shariah-Certified Hos - Sagiran, - (International Journal of Human and Health Sciences (IJHHS), 2024)
Introduction and Purposes: In Indonesia, Shariah Hospital certification is a pioneering fusion of Maqashid Sharia principles and the National Hospital Accreditation Commission format, resulting in a comprehensive set of standards applied in Shariah- certified Hospitals. These hospitals have evolved to cater to the predominantly Muslim population, bridging the gap between faith and modern healthcare. They prioritize unwavering Shariah compliance, emphasizing critical control points and comprehensive standards. This approach enhances value by aligning services with religious beliefs, fostering collaborations, and elevating satisfaction. Furthermore, these hospitals play a crucial role in promoting community well-being through robust charity networks. Their dynamic and progressive approach positions them as leaders in healthcare excellence, seamlessly uniting faith and modern medicine. Approach and Value: Shariah Hospital certification is based on the 2015 Standard of Shariah Hospital Certification published by the MUI and MUKISI Sharia Council, encompassing 62 standards and 201 assessment elements. This process ensures religious adherence and enhances the value of these hospitals from multiple perspectives. Additionally, it establishes a network for charitable programs, including CSR, Dakwah, Zakat, and Wakaf, significantly contributing to community well-being. The ongoing development and updates of these hospitals underscore their dynamic and progressive approach, positioning them as healthcare excellence leaders, adept at harmonizing faith and modern medicine. These Shariah hospitals offer numerous benefits, ensuring patient comfort with guaranteed halal healthcare and halal salaries for workers, along with opportunities for collaboration with CSR and waqf institutions, access to development funding,and donations. Presently, Indonesia boasts 77 Sharia Hospitals, including 3 Sharia Certified Hospitals, 30 in the Pre-Survey and Assistance Process, and 16 Hospitals Registering for Assistance. This approach aims to expand the concept of Sharia Hospitals globally, especially in Muslim-majority countries, to promote healthcare excellence rooted in faith. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S28